Development of an in vitro system to study chromatin remodeling and transcription activation of the Saccharomyces cerevisiae PHO5 gene - Terrell, Andrea R., author; Laybourn, Paul, advisor (Colorado State University. Libraries, 1999)
The Saccharomyces cerevisiae PHO5 gene encodes the major secreted acid phosphatase in yeast. Expression of PHO5 is regulated through its chromatin structure by phosphate availability. The gene is repressed when there is adequate phosphate in the environment and becomes activated upon phosphate starvation. There are four translationally positioned nucleosomes located over the PHO5 promoter. All four nucleosomes become nuclease transparent upon transcription activation via the actions of Pho4p and Pho2p, two DNA binding transcription activators. To investigate the mechanism of activation of PHO5, an in vitro system was designed that utilizes purified yeast core histones and transcription activators, yeast extracts, and a plasmid template containing the PHO5 promoter. This dissertation describes the use of this system to study the mechanisms of transcription activation and nucleosome remodeling on the PHO5 promoter. Through in vitro transcription assays, I have determined that purified recombinant Pho4p activates transcription on naked DNA but is not sufficient to counteract the nucleosome repression of PHO5. Using primer extension footprinting on in vitro reconstituted chromatin, Pho4p and Pho2p were shown to bind the PHO5 promoter regardless of whether it existed as naked or chromatin DNA. I have also used micrococcal nuclease digestion to determine that chromatin is being remodeled by the same whole cell extract used for transcription assays, therefore the lack of derepression on chromatin templates is most likely a result of another unidentified barrier, possibly to elongation. I have also shown that fractionated nuclear extract can remodel PHO5 chromatin and that the requirements for remodeling are different depending on the amount of extract added. Unfortunately, the results presented in this dissertation fail to provide a clear understanding of nucleosome remodeling and transcription activation of PHO5. However, a great deal of time and effort has gone into this project and I believe this system, since it is now very well defined, will be a useful tool in future studies of gene regulation in the context of chromatin.
Keywords: biochemistry; molecular biology; genetics